Pengendang Perempuan Dalam Karawitan Jawa Pengiring Perayaan Ekaristi di Gereja Pugeran Yogyakarta - Andaru Kumara Jati (Institut Seni Indonesia Yogyakarta, 2018)
Eucharist is a sacred and the primary ritual for Catholics, it has adapted to the local culture. This adaption process called inculturation. Some examples of inculturation that is language and music. In Sacred Heart of Jesus Catholic Church Pugeran Yogyakarta, inculturation appears with the eucharist with Javanese language and Javanese songs with Javanese musical accompaniment called gamelan. Gamelan is a set of musical instruments that have undergone many developments. Gamelan played generally by men, because the gamelan construction is designed to be played by sitting of male style. But today there’s more and more groups of gamelan involving women as a player. In Pugeran Church found the phenomenon of female kendang (drums) player. This woman has a position as a leader, and it is in contrast to Javenese culture which has patriarchal principle, so that in this research examined the cause of the female kendang player in Catholic church and her performances.The method used in this research is descriptive method of analysis that describes the object in writing and detail. The research is qualitative research with ethnomusicological approach that explores the object not only the form of music (textual) but also all related cultural aspects (contextual). In addition, this research also uses a sociological and theological approach that helps to explore from a socio-cultural point of view and the science of Catholicism. Search data consists by literature study, observation, interviews and documentation. All data is done from October 2017 until June 2018. This research using gender theory in The Social Psychology of Music by David J. Hargreaves and Adrian C. North to analyze the data and answer the problems.